GAMBARAN SANITASI DAN PERSONAL HYGIENE KANTIN SEKOLAH DI WILAYAH KERJA PUSKESMAS BANJARNEGARA I TAHUN 2024 - Anis Supriyatin; Joko Malis Sunarno (Jurnal Ilmiah Medsains, 2024)
Food is a basic human need for survival, therefore it must be healthy, and free from bacterial contamination and toxic substances. Food can be a source of disease transmission if hygiene is not maintained properly during food handling and food hygiene is not observed during food processing. Food sanitation is important for canteen managers to pay attention to, especially school canteens which provide large quantities of food and have a high level of consumers. The aim of this research is to find out the description of sanitation and personal hygiene of school canteens in the working area of Banjarnegara Health Center 1.             This research is descriptive with a cross sectional method. The population includes school canteen food handlers in the work area of Puskesmas Banjarnegara 1 who sell their food in school canteens in June 2024, namely 20 school canteens with sampling using the random sampling method. The data used in this research are primary data obtained from interviews and field observations as well as secondary data from Puskesmas Banjarnegara 1.             The results of this study show that the majority of food handlers are female (95%), aged 15-40 at most (60%), have at least junior high school education (50%), canteen sanitation is in the good category (55%), personal hygiene in the good category (100%) and existing regulations (25%).             This research shows that sanitation is mostly good and overall personal hygiene is good. Food handlers are expected to pay more attention to food sanitation, especially by providing hand washing facilities with soap and providing rubbish bin facilities.